2016
DOI: 10.1101/085068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neural basis of precise visual short-term memory for complex recognisable objects

Abstract: Recent evidence suggests that visual short-term memory (VSTM) capacity estimated using simple objects, such as colours and oriented bars, may not generalise well to more naturalistic stimuli. More visual detail can be stored in VSTM when complex, recognisable objects are maintained compared to simple objects. It is not yet known if it is recognisability that enhances memory precision, nor whether maintenance of recognisable objects is achieved with the same network of brain regions supporting maintenance of si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Similar perceptual 'overwriting' processes have been observed in other studies (Enns & Di Lollo, 2000;Lakha & Wright, 2004, see also Logie, 1995;Phillips & Christie, 1977;Wilson, Scott, & Power, 1987). Furthermore, complex recognizable items were associated both with better memory precision and appeared supported by a richer range of neural representations than unrecognizable objects, suggesting that recognizable objects evoked richer and more variable contextual associations (Veldsman, Mitchell, & Cusack, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…Similar perceptual 'overwriting' processes have been observed in other studies (Enns & Di Lollo, 2000;Lakha & Wright, 2004, see also Logie, 1995;Phillips & Christie, 1977;Wilson, Scott, & Power, 1987). Furthermore, complex recognizable items were associated both with better memory precision and appeared supported by a richer range of neural representations than unrecognizable objects, suggesting that recognizable objects evoked richer and more variable contextual associations (Veldsman, Mitchell, & Cusack, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…Critically, by asking participants whether they perceived the stimuli as a face or not, that study also showed that enhancements in active maintenance of items in visual working memory are due to the subjective perception of the stimulus as meaningful, and are not driven by physical properties of the stimulus. Evidence from fMRI is also consistent with these results: for example, Veldsman et al (2017) found evidence of richer representations in critical working memory regions in parietal cortex for meaningful rather than perceptuallymatched non-meaningful stimuli; and Stojanoski et al (2019) found evidence that meaningful stimuli were processed in more high-level ventral regions in preparation for visual working memory storage than perceptually-matched non-meaningful stimuli.…”
Section: Active Neural Representationmentioning
confidence: 55%
“…For example, in other recent work, we have shown that a major reason not all studies have found object benefits at long encoding times (e.g., Quirk et al 2020;Li et al 2020) is that they chose foils unfairly, in a way that disadvantages objects relative to colors (Brady & Störmer, 2020). Once this is accounted for, significant benefits for memory performance with real-world objects emerge reliably compared to both colors (Brady & Störmer, 2020) and perceptually-matched meaningless stimuli (e.g., Brady & Störmer, 2020;Stojanoski et al 2019;Veldsman et al 2017;Sahar et al 2020). In addition, verbal re-encoding is always a potential concern with long encoding times, and studies have differed in how they have prevented this (e.g., Quirk et al 2020, Li et al 2020Brady et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The neural substrate of attentional and short-term (<5-min) memory function is diffusely distributed (Cohen and Maunsell, 2011;Zhou and Desimone 2011;Zhang et al, 2011;Luo and Maunsell, 2015;Veldsman et al, 2017). While both attentional and short-term memory function involve the prefrontal cortex, including premotor cortex (Rizzolatti et al, 1987;Bichot et al, 2015;Chen et al, 2017;Barthas and Kwan 2017;Moore 2006), there is no clearly defined fiber bundle to specifically examine the axons relevant to these cognitive behavioral functions.…”
Section: Discussionmentioning
confidence: 99%